Programmable Assembly of Colloidal Nanoparticles Controlled by Electrostatic Potential Well. Issue 10 (21st August 2022) - Liu, Yuanlan; Wang, Yawen; Sun, Yinghui; Li, Dong; Liang, Zhiqiang; Liang, Wenkai; Gao, Heng; Qin, Wei; Qian, Hongqiang; Jiang, Lin
Abstract : Compared with the individual colloidal nanoparticles, programmable nanoassemblies with well‐defined configurations exhibit more prominent coupling effects and collective behaviors. The full realization of the unique superiority of these nano assemblies requires the development of feasible approaches to assemble colloidal nanoparticles into an organized nanostructure on substrates, which remains a major challenge in nanotechnology at present. Herein, a facile strategy is developed to programmatically design diversified nanostructures through the rational capture of nanoparticles with flexibly adjustable particle types, including their sizes, shapes, or components. Importantly, such a strategy takes advantage of a bowl‐shaped electrostatic potential well that forms based on the combination of a positively charged nanoparticle and a negatively charged substrate, where theory and simulation are employed to reveal the notable role of the substrate potential. As a demonstration, a series of nanostructures with customized geometries and locations have been successfully fabricated, especially the asymmetric dimer structures, which bring about distinct localized surface plasmon resonance hybridization and coupling effects. Therefore, the joint computational–experimental showcase paves the way toward the preparation of ideal nanostructures, providing valuable insight into the development of optical encryption, smart sensing, sensitive bio‐detection, and so on. Abstract : A bowl‐shaped electrostatic potential well can be formed based on the combined effects of a positively charged nanoparticle and a negatively charged substrate. The regulation of substrate potential will change the state of the electrostatic potential well, thus controlling the rationed capture of negatively charged nanoparticles and the programmable assembly of the colloidal nanostructures.